Respiratory sensory gating measured by respiratory-related evoked potentials in generalized anxiety disorder - Chan, Pei-Ying S.; Cheng, Chia-Hsiung; Hsu, Shih-Chieh; Liu, Chia-Yih; Davenport, Paul W.; Leupoldt, Andreas von (Frontiers in Psychology, 2015)
The perception of respiratory sensations plays an important role both in respiratory diseases and in anxiety disorders. However, little is known about the neural processes underlying respiratory sensory perception, especially in patient groups. Therefore, the present study examined whether patients with generalized anxiety disorder (GAD) would demonstrate altered respiratory sensory gating compared to a healthy control group. Respiratory-related evoked potentials (RREP) were measured in a paired inspiratory occlusion paradigm presenting two brief occlusion stimuli (S1 and S2) within one inspiration. The results showed a significantly greater S2/S1 ratio for the N1 component of the RREP in the GAD group compared to the control group. Our findings suggest altered respiratory sensory processing in patients with GAD, which might contribute to altered perception of respiratory sensations in these patients.